Application Of Oxytocin Massage In Spontaneous Post Partum Mothers To Increase Breast Milk Production - Elis Roslianti; Ade Fitriani; Tiara Cahya Rinukti (LPPM STIKes Muhammadiyah Ciamis, 2021)
Objective: The purpose of this case study was to determine the effectiveness of oxytocin massage in post partum mothers to increase milk production.Method: The method used is a descriptive analysis design in the form of a case study with a mathematic nursing care process approach which includes assessment, diagnosis, planning, implementation, and evaluation. The subjects used in this study were clients who had problems with Ineffective Breastfeeding in the Teratai 2 Room BLUD RSU Banjar City. With data collection techniques including interviews, observation, physical examination, and documentation studies.Result: This case study is supported by objective data and subjective data. The objective data obtained were that the patient admitted that the breasts did not feel tight, the breasts were clean, there were no lesions and redness, blood pressure 120/80 mmHg, temperature 36.6°C, pulse 86x/minute, respiration 20x/minute. While subjective data, namely the recognition of patients complaining of very little milk expenditure.Conclusion: There is an effect of oxytocin massage on milk production in spontaneous post partum mothers. It is expected that mothers who experience irregular milk production will routinely perform massage actions to expedite milk production.